If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4n + 1) = 8 Reorder the terms: -4(1 + 4n) = 8 (1 * -4 + 4n * -4) = 8 (-4 + -16n) = 8 Solving -4 + -16n = 8 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -16n = 8 + 4 Combine like terms: -4 + 4 = 0 0 + -16n = 8 + 4 -16n = 8 + 4 Combine like terms: 8 + 4 = 12 -16n = 12 Divide each side by '-16'. n = -0.75 Simplifying n = -0.75
| -8*-8= | | 9w+15=3w+45 | | 10(z+4)-4(z-2)=3(z-1)+2(-3) | | z^2+13z+42=0 | | x-0.2x=21.60 | | -4(3n+5)=8 | | 0.5(5x+8)=1.1-(x-3) | | -15+7= | | x-.2=21.60 | | 28x^2+17x-3=6 | | -4x-1=-2x+10 | | -7+3a=7a-3 | | 28x^2+17x+3=6 | | 6(7q-5)-[3(5q-3)+2]= | | x+2x=-24 | | h+2=2(k+2) | | x+2x=-34 | | 20+x=2x-44 | | 4.06(x-14)-2.2x=99.40 | | 2.5(3j-1)=-25 | | 0.6+0.6=-8 | | 5(2z-1)-2(z+3)=3(z+1) | | s=(27-b)(20+b) | | 3(8x-2)-6(5+4x)=0 | | 5(2z-1)-2(z+3)=(z+1) | | 0.2v=0.6v+1.7 | | 6(5+c)=5(c-6) | | 0.4w+0.6=-3 | | 11(6c-1)-2=64c+11 | | 6(y-2)=2y-40 | | 4-6x=13+3x | | -3y-9=5y+15 |